GLOBAL EXPERIENCE OF PUBLIC ADMINISTRATION IN THE TOURISM SECTOR - Rushchenko, Yevhen (Public Management and Policy, 2025)
The purpose of the study is: to consolidate contemporary approaches to tourism regulation in countries with varying levels of development; to assess smart governance models in tourist destinations; to identify key factors influencing the success or failure of tourism policy; and to develop practical recommendations for enhancing public management in the tourism sector in Ukraine, drawing on international experience. This article explores the global experience of public administration in the tourism sector, focusing on the governance models implemented in leading countries such as France, Spain, Italy, Turkey, China, the United States, Canada, and Japan. The study emphasizes the role of government institutions, the decentralization of powers, inter-agency cooperation, and public-private partnerships in shaping effective tourism policies. The author analyzes strategic planning practices, destination marketing approaches, legislative frameworks, and the operation of national tourism organizations. Particular attention is given to the integration of information technologies in public administration and the implementation of sustainable tourism development principles. The article highlights the strengths and weaknesses of different governance models and identifies key success factors in tourism policy, including institutional, economic, cultural, and geographical dimensions. Through comparative analysis, the authors develop recommendations for improving the system of state governance of tourism in Ukraine, taking into account both international best practices and domestic realities. The conclusion emphasizes the necessity of a systematic approach to forming public tourism policy. This approach should include the integration of stakeholder interests, enhanced decision-making efficiency, infrastructure development, investment in human capital, and ensuring the environmental and social sustainability of the tourism sector.